Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1093/cid/cix1081
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Safety and Immunogenicity of Influenza Vaccination Strategies in Solid Organ Transplant Recipients

Abstract: Immunogenicity from seasonal inactivated influenza vaccine (IIV) remains suboptimal in solid organ transplant recipients (SOTRs). We conducted a systematic review that compared the safety and immunogenicity of nonstandard influenza vaccination strategies with single-dose IIV in SOTRs. Booster doses and possibly high-dose (HD) influenza vaccination strategies seem to hold promise for improving vaccination immunogenicity in SOTRs. Administration of intradermal and MF59-adjuvanted trivalent IIV (IIV3) did not imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 26 publications
0
27
0
2
Order By: Relevance
“…36 Influenza vaccine is well tolerated in SOT recipients, and adverse events to vaccination are usually mild and short lived. 41 Recent randomized controlled trials found increased immunogenicity in SOT recipients using a highdose vaccine or a booster strategy using two doses of the standard dose vaccine 5 weeks apart. 42,43 These approaches can be particularly used in case of an expected lower response to the vaccine due to en hanced immunosuppression.…”
Section: Prevention/prophylaxismentioning
confidence: 99%
“…36 Influenza vaccine is well tolerated in SOT recipients, and adverse events to vaccination are usually mild and short lived. 41 Recent randomized controlled trials found increased immunogenicity in SOT recipients using a highdose vaccine or a booster strategy using two doses of the standard dose vaccine 5 weeks apart. 42,43 These approaches can be particularly used in case of an expected lower response to the vaccine due to en hanced immunosuppression.…”
Section: Prevention/prophylaxismentioning
confidence: 99%
“…Influenza vaccination can induce antibody mediated rejection by increasing donor specific anti-human leukocyte antigen (HLA) antibodies (DSA) ( 16 20 ). Recognition of donor HLA in the graft by recipient’s T cells can stimulate allograft rejection by the activation of a pro-inflammatory response that includes the activation of B cells producing DSA that can be associated with the development of chronic allograft injury ( 21 , 22 ). In addition, using strategies to increase vaccination efficacy (high-dose vaccines, booster doses, and adjuvanted vaccines) may contribute to increased allograft rejection and graft dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…There were evidences that HSCT population could benefit from vaccination [35][36][37][38], and the latest recommendation was to start inactivated vaccines from 3 months after transplant [39]. However, a systematic review showed that seasonal inactivated influenza vaccine remained suboptimal in SOT recipients [40]. No consensus guidelines on influenza vaccination for patients with malignancies, but timing of vaccination was recommended more than two weeks before receiving chemotherapy or between chemotherapy cycles in order to enhance humoral responses [3].…”
Section: Discussionmentioning
confidence: 99%